2022
DOI: 10.36722/sst.v7i1.1042
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Pengetahuan dan Kepatuhan Sivitas Akademika Universitas Al-Azhar Indonesia dalam Membaca Label Pangan

Abstract: <p><strong>The busyness and lifestyle of modern society today tends to like instant things, including choosing food products. This is because packaged food products are more practical, easy to carry, widely available, and easy to consume. An analysis is needed regarding the level of knowledge and compliance of the community, especially the academic community of University Al-Azhar Indonesia (UAI) in this regard, so that the community can increase knowledge and compliance in reading packaged food la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…Meanwhile, age has a significant value of 0.667, where the significant values are both greater than 0.05, so it can be concluded that demographic factor variables (gender and age) cannot predict the behavior of reading halal labels among students in Bangkalan district, so it can concluded that 𝐻 0 rejected, 𝐻 𝑎 accepted. Based on this, it is in line with research by Widiawati et al (2022) who said that there was no relationship between individual characteristics such as gender, age and education level and the level of respondent compliance in reading labels on packaged food products. However, this research is not in line with research conducted by Simanjutak…”
Section: Interpretation Of Resultssupporting
confidence: 87%
“…Meanwhile, age has a significant value of 0.667, where the significant values are both greater than 0.05, so it can be concluded that demographic factor variables (gender and age) cannot predict the behavior of reading halal labels among students in Bangkalan district, so it can concluded that 𝐻 0 rejected, 𝐻 𝑎 accepted. Based on this, it is in line with research by Widiawati et al (2022) who said that there was no relationship between individual characteristics such as gender, age and education level and the level of respondent compliance in reading labels on packaged food products. However, this research is not in line with research conducted by Simanjutak…”
Section: Interpretation Of Resultssupporting
confidence: 87%